Does location matter in determining firms' performance? A comparative analysis of domestic and multinational companies. Issue 3 (6th August 2018) - Shah, Said; Anwar, Jamil; Hasnu, SAF
Abstract : Purpose: The purpose of this paper is to investigate the impact of internationalization of investment on corporate policies through multinational firms (MNFs) and thereby variation in financial performances when compared to domestic firms (DFs) using 10 years' (2004-2013) secondary data of 153 firms listed on Pakistan Stock Exchange. Design/methodology/approach: This study applies regression and ratio analyses for testing of hypotheses and other statistics. Findings: The results indicate that the performance of MNFs is better than that of DFs primarily because of internationalization of investments and inventory utilization. The rest of the factors included in the model, namely, cash conversion cycle and corporate governance (CG) indices, have less prominent role in determining firms' performance. Research limitations/implications: Sample size was restricted to 153 firms, as complete data for the period selected to carry out the study were available only for these firms. For determining the quality of CG, only sample average has been used as bench mark due to non-availability of industrial average. Practical implications: The recommendations of the research can be used by economic planners and corporate experts as policy guidelines and bench mark for improving the corporate and economic performance of the country. Besides, these recommendations are beneficial for emerging economies particularly and developed economies generally across the globe. Social implications: Economic and financial regulators can get guidance from the findings of the study to adjust national-level corporate planning. For example, State Bank of Pakistan (the central bank of the country) can amend its prudential regulations with regard to maintaining liquidity by corporate units according to the results of the study. Corporate units can directly get guidance and adopt the findings of the study in their corporate planning to improve their performance. The findings and methodology of the research can also be used by research students on further exploring the field. Originality/value: Splitting the sample into domestic and multinationals firms, separately and jointly analyzing these firms and then comparing corporate strategies of these firms based on location are unique.